أثر أسلوب المطالعة الخارجیة في تعدیل الفھم الخاطئ للمفاھیم العلمیة في مادة العلوم لطلاب الصف الأول المتوسط في ثانویة كلیة بغداد (Journal of the College of Education for Women, 2019)
The aim of the research :Current research aims is to present the effect of how the style of reading to amend the wrongunderstanding of scientific conceptsIn the lesson of science for the first grade in Baghdad faculty secondary school.To achieve this goal has been formulated the following null hypothesis :-" there is no statistically differences at the level of (0.05) between the average at level ofstudents achievement in the style of reading comprehension "In order to validate the hypothesis by conducting an experiment had started from 19/3/2011-1/5/2011 for the second semester.After the researcher prepared suplies for the researcher prepared suplies for the experience anddeternim the scientific material contained ,limited to scientific concepts and the development ofbehavioral objects and writing teaching plans .The tools of the research :Research tooll has been prepared and tested for the diagnosis of the mistuned standingscientific concepts , (24) concepts, each concepts measured by three paragraphs(definition ,example and application ) so that the test consist of 72 varied between the paragraph and short essayto the substantive .The sample of the study:The random selection of first grade section (b) that has (17) students from Baghdad facultysecondary school in Al- kharkh 2nd Baghdad education the recent research have two phases .1- diagnostic phase :-After the application of the diagnostic test ,which way the diagnostic is the scientific conceptsthat are misunder standing by the students (the sample of the study ), it is found that there are (12concepts) have mistaken by the students with 34% have been distributed in the subjects of the booknamed (General sciences on public sciencer).2-phase of treatment.This face have been measured by the application the method of "the style of reading accordingto the newest style of reading comprehension . After all the student studied all the items of thesubjects book of "General sciences on public sciencer " the group has been tested with understanding of scientific concept at the wrong dimensional data method analysis showed the results ofpost – test of the scientific concept .the average of the student grades is (%79.6)and the standarddeviation (2.4) and with using of (t- test ) it is appeared that the calculated t- value is (12.6) that isbigger than the (tabulated value ) (12.12o) at the level of the significance (0.05) and freedom degree(16) .And this reject and thus rejects the null hypothesis .Conclusion :The most important finding of the researcher in this study is that the use ofexternal style of reading was active in modifying the wrong understanding of scientific research hasbeen to for mulated a number of recommendations and proposales.